Analyzing Milk Caramel Candy with the Addition of Emprit Ginger and Secang Wood Extract - Rahayu, Sri; Rosidah, Rosidah; Paramita, Octavianti; Ansori, Muhammad; Setiani, Bhakti Etza (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
This study added Emprit ginger extract and Secang wood extract to milk caramel candy. Adding Emprit ginger extract and Secang wood extract was expected to add nutritional value to milk caramel candy. The objectives of this study include (1) knowing the effect of adding Emprit ginger extract and Secang wood extract on the sensory quality of milk caramel candy, (2) finding out what people like, and (3) knowing the nutritional content in the form of water content and flavonoid content. The independent variable in this study was the addition of Emprit ginger extract and Secang wood extract, which were not the same, namely samples A (5%), B (7.5%), and C (10%). The data collection method in this study is to use subjective assessments, namely sensory tests and favorability tests, as well as objective assessments, namely laboratory tests of water and flavonoid content. The analytical method used in sensory tests is simple linear regression. The results showed an influence on the sensory quality of the experimental milk caramel candy in terms of color, aroma, texture, and taste. In the preference test sample, A has the highest average value in all aspects, and the sample with the lowest average value is sample C. The results of laboratory tests of water content in sample K were 2.91%, sample A was 4.26%, sample B was 5.62%, and sample C was 7.08%. Laboratory test results of flavonoid content of sample K are 0%, sample A as much as 0.16%, sample B as much as 0.24%, and sample C as much as 0.31%.